Powerskating as an impact on the development of chosen game activity of individual in ice hockey in older students´ team HC´ 05 Banská Bystrica - Opath, L. (Acta Universitatis Matthiae Belii, Physical Education and Sport, 2013)
The aim of the study was to determine how powerskating influences the game of an individual player - ice skating in the category of older students in the Ice Hockey team HC 05 Banská Bystrica. We have included powerskating exercises into training process of experimental group HC´ 05 Banksá Bystrica. These exercises were not made in control group. We performed skating test of Slovak Ice Hockey Federation in both groups and we compared the obtained results between the experimental and the control group. The results have shown, that powerskating which was implemented into the training process of experimental group, was important for improving the level of chosen game activity of an individual - ice skating. Our assumptions of positive influence of powerskating on skating of players were confirmed. We hope that positive results of our research will contribute to the improvement of training and development of the game activity of an individual in the area of ice skating.